Formation of Biphasic State in Vacuum-Arc Coatings Obtained by Evaporation of Ti-Al-Zr-Nb-Y Alloy in the Atmosphere of Nitrogen - V.M. Beresnev; O.V. Sobol; I.N. Toryanik; A.A. Meylekhov; U.S. Nyemchenko; P.V. Turbin; I.V. Yakushchenko; M.O. Lisovenko (Журнал нано- та електронної фізики)
By means of X-ray diffraction, transmission and scanning electron microscopy, energy dispersive spectroscopy and indentation methods, the effect of nitrogen atmosphere pressure on composition, structure and hardness of vacuum-arc (Ti-Al-Zr-Nb-Y)N coatings during the deposition process has been studied. The two-phase state of the coating with solid-solution metal component (bcc lattice) and nitride phase (fcc lattice) have been formed. Increasing the pressure of nitrogen atmosphere leads to the increase of nitrogen component in the coating as well as to increase of the ordering regions size, allowing to achieve the hardness of H = 49 GPa at a pressure of P = 0.5 Pa.